Preparation method of solid electrolyte membrane and solid-state battery
Patent Information
- Application Number
- CN202310511361.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-06
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-05-06
AI Technical Summary
[0003]目前,固态电解质层的制备方法包括:湿法浇注成膜以及干法成膜;其中,湿法浇注成膜为了提高成膜强度,粘接剂的添加量需为2%-5%,溶剂挥发后膜材孔隙率为20%-40%,如此电解质膜表面形变能力差,与活性物质层之间的界面需要依靠很大的压力才能够压制精密,电池的加工难度大,影响固态电池的容量发挥和工艺放大;干法成膜的膜材孔隙率为10%-30%,且膜材表面已被充分辊压至光亮状态,这说明表面颗粒已被压紧,与活性物质层贴合时不再有形变空间,导致界面接触较差,容量发挥不良
[0041]本发明制备方法制得的固态电解质膜密度低,柔性高,塑形好,与活性物质层界面接触更紧密;包括前述固态电解质膜的固态电池在首周效率以及首周放电容量上具有显著提升。
Smart Images

Figure CN116525927B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a method for preparing a solid electrolyte membrane and a solid battery. Background Technology
[0002] Compared to traditional liquid batteries, solid-state batteries have high energy density and high safety because they use a solid electrolyte instead of a separator in liquid batteries and do not require the addition of electrolyte. Lithium-ion transport is accomplished through a solid electrolyte layer with high ionic conductivity. However, the lack of sufficient wetting of the active material by the electrolyte makes the interfacial transport of lithium ions between the active material and the solid electrolyte a major problem that needs to be solved.
[0003] Currently, the preparation methods for solid electrolyte layers include wet casting and dry casting. In wet casting, to improve film strength, the amount of binder added needs to be 2%-5%, and the porosity of the film material after solvent evaporation is 20%-40%. This results in poor surface deformation ability of the electrolyte film, and the interface between it and the active material layer requires a lot of pressure to be pressed precisely, making the battery processing difficult and affecting the capacity performance and process scale-up of solid-state batteries. In dry casting, the porosity of the film material is 10%-30%, and the surface of the film material has been fully rolled to a bright state. This means that the surface particles have been compacted, and there is no room for deformation when it is bonded to the active material layer, resulting in poor interface contact and poor capacity performance.
[0004] Therefore, there is an urgent need for a method for preparing solid electrolyte membranes and solid-state batteries. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a method for preparing a solid electrolyte membrane and a solid-state battery.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] The first aspect of this invention is to provide a method for preparing a solid electrolyte membrane, comprising the steps of: subjecting a mixture of electrolyte and binder powder to rolling several times to obtain the solid electrolyte membrane; wherein,
[0008] In the initial rolling process, the speed ratio between the first and second rollers is 1.2-10; and
[0009] In the final rolling process, the gap between the first roller and the second roller is 15μm-50μm; and
[0010] In each rolling process, the speed ratio of the first roller to the second roller is lower than that in the previous rolling process, and the speed ratio of the first roller to the second roller is greater than 1; or, in each rolling process, the gap between the first roller and the second roller is lower than that in the previous rolling process; or, in each rolling process, the speed ratio of the first roller to the second roller is lower than that in the previous rolling process, and the speed ratio of the first roller to the second roller is greater than 1, while the gap between the first roller and the second roller is lower than that in the previous rolling process.
[0011] Preferably, the electrolyte includes at least one of oxide electrolyte, sulfide electrolyte, halide electrolyte or polymer electrolyte.
[0012] Furthermore, the oxide electrolyte includes at least one of LATP, LLZO, or LLZTO.
[0013] Furthermore, the sulfide electrolyte includes at least one of LiPSCl, LiPSBr, LiSiPS, or LiGePS.
[0014] Furthermore, the halide electrolyte includes at least one of Li3InCl6, Li3YCl6, or Li3YBr6.
[0015] Furthermore, the polymer electrolyte includes at least one of PEO electrolytes, PVDF-HFP electrolytes, or PFEC electrolytes.
[0016] Preferably, the adhesive comprises at least one of polytetrafluoroethylene, styrene-butadiene-styrene block copolymer, polyvinylidene fluoride, polyvinylidene fluoride copolymer, cellulose, nitrile rubber, or modified rubber.
[0017] Preferably, the mass ratio of the electrolyte to the adhesive is (95-99.9):(0.1-5).
[0018] Preferably, the preparation step of the mixed powder of the electrolyte and the binder includes:
[0019] S1-0, Take the electrolyte in powder form and the adhesive in powder form;
[0020] S1-1. The electrolyte and the binder are mixed at a first temperature and a first speed to obtain an intermediate powder.
[0021] S1-2, At a second temperature and a second speed, the intermediate powder is mixed a second time to obtain the mixed powder; wherein,
[0022] The first temperature is lower than the second temperature, and the first speed is lower than the second speed.
[0023] Preferably, the first mixing process ensures that the electrolyte and the binder are sufficiently and uniformly dispersed to obtain an intermediate powder.
[0024] Preferably, the second mixing causes the binder in the intermediate powder to filamentize, so as to coat the particles in the intermediate powder into a marshmallow-like shape.
[0025] Preferably, the first temperature is room temperature.
[0026] Preferably, the first speed is 1 rpm to 100 rpm.
[0027] Preferably, the second temperature is 30℃-80℃.
[0028] Preferably, the second speed is 1000rpm-10000rpm.
[0029] Preferably, the mixed powder further includes a solvent for promoting migration between powder particles, wherein the solvent does not react with the electrolyte or the binder.
[0030] Preferably, after the mixed powder undergoes several rolling processes, the solvent is removed by drying.
[0031] Preferably, the solvent includes at least one of toluene, xylene, or anisole.
[0032] Preferably, the mixture of electrolyte and binder powder is subjected to several rolling processes at a temperature of 20°C to 100°C.
[0033] Furthermore, the mixture of electrolyte and binder powder is subjected to several rolling processes at 50℃-60℃.
[0034] Preferably, the number of times the rollers are pressed is no more than 3.
[0035] Furthermore, the rolling process is performed twice; in the first rolling process, the speed ratio between the first roller and the second roller is 2-3, and the gap between the first roller and the second roller is 150μm-200μm; in the last rolling process, the speed ratio between the first roller and the second roller is 1.1-1.5, and the gap between the first roller and the second roller is 30μm-50μm.
[0036] Furthermore, the rolling process is performed three times; in the first rolling process, the speed ratio between the first roller and the second roller is 3-5, and the gap between the first roller and the second roller is 150μm-300μm; in the second rolling process, the speed ratio between the first roller and the second roller is 1.8-3, and the gap between the first roller and the second roller is 50μm-100μm; in the final rolling process, the speed ratio between the first roller and the second roller is 1.1-1.5, and the gap between the first roller and the second roller is 30μm-50μm.
[0037] Preferably, the diameter of the first roller and the second roller is 12cm-20cm.
[0038] Preferably, the radial runout of the first roller and the second roller is not higher than ±2μm.
[0039] A second aspect of the present invention is to provide a solid-state battery comprising: a solid electrolyte membrane prepared by the preparation method described above.
[0040] The present invention adopts the above technical solution and has the following technical effects compared with the prior art:
[0041] The solid electrolyte membrane prepared by the method of the present invention has low density, high flexibility, good plasticity, and closer contact with the active material layer interface; solid batteries including the aforementioned solid electrolyte membrane have significant improvements in first-cycle efficiency and first-cycle discharge capacity. Attached Figure Description
[0042] Figure 1 The graphs show the EIS detection results of Examples 1-3 and Comparative Examples 1-2 in the fully charged state of this invention. Detailed Implementation
[0043] The specific embodiments of the present invention will be described in detail below.
[0044] Unless otherwise defined, the technical or scientific terms used in the claims and description shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.
[0045] The word "comprising" or similar terms used in the specification and claims of this patent application mean that the objects preceding "comprising" include the objects listed after "comprising" or their equivalents, and do not exclude other objects.
[0046] The numerical values mentioned in this invention include all values increasing one unit at a time from low to high, assuming that there is at least a two-unit interval between any lower and higher value. For example, if it is said that a component quantity or a physical quantity is better from 1 to 100, 10 to 90, and 20 to 80, it means that values such as 5 to 95, 14 to 76, 23 to 67, 32 to 58, and 41 to 49 are clearly listed in this specification; for values less than 1, 0.0001, 0.001, 0.01, or 0.1 are considered to be a suitable unit. The foregoing examples are for illustrative purposes only; in practice, all combinations of values between the lowest and highest listed values are considered to be clearly listed in this specification in a similar manner.
[0047] This embodiment provides a method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0048] S1-0, Take powdered electrolyte and powdered binder;
[0049] S1-1. At room temperature, the electrolyte and the binder are mixed at 1 rpm to 100 rpm to fully and uniformly disperse the electrolyte and the binder, resulting in an intermediate powder.
[0050] S1-2. At 30℃-80℃, the intermediate powder is mixed for the second time at 1000rpm-10000rpm to fibrillate the binder in the intermediate powder, so as to coat the particles in the intermediate powder into a marshmallow-like shape, thus obtaining a fluffy mixed powder.
[0051] S2-0, Provide a roller press; or, provide a roller press assembly, the roller press assembly comprising: the roller press; the roller press comprising: a first roller, a second roller, a first motor for driving the first roller, and a second motor for driving the second roller, the first motor and the second motor respectively driving the first roller and the second roller to achieve opposite-direction, non-uniform rotation of the first roller and the second roller; wherein...
[0052] The first roller is a movable roller, and the second roller is a fixed roller; or, the first roller is a fixed roller, and the second roller is a movable roller; or, the first roller is a movable roller, and the second roller is a movable roller.
[0053] Both the first roller and the second roller are horizontal rollers to facilitate material feeding;
[0054] The diameter of the first roller and the second roller is 12cm-20cm, and the radial runout of the first roller and the second roller is no higher than ±2μm;
[0055] S2-1, The mixed powder is subjected to 2-3 gradient rolling processes at 20℃-100℃ to form the solid electrolyte membrane; wherein,
[0056] In the initial rolling process, the speed ratio between the first and second rollers is 1.2-10; and
[0057] In the final rolling process, the gap between the first roller and the second roller is 15μm-50μm; and
[0058] In each rolling process, the speed ratio of the first roller to the second roller is lower than that in the previous rolling process, and the speed ratio of the first roller to the second roller is greater than 1; or, in each rolling process, the gap between the first roller and the second roller is lower than that in the previous rolling process; or, in each rolling process, the speed ratio of the first roller to the second roller is lower than that in the previous rolling process, and the speed ratio of the first roller to the second roller is greater than 1, while the gap between the first roller and the second roller is lower than that in the previous rolling process.
[0059] The resulting solid electrolyte membrane had a thickness of 30 μm-90 μm and a density of 1.0 g / cm³. 3 -2.5g / cm 3 The porosity is 30%-50%.
[0060] In a preferred embodiment, the electrolyte includes at least one of the following: oxide electrolytes, such as LATP, LLZO, or LLZTO; sulfide electrolytes, such as LiPSCl, LiPSBr, LiSiPS, or LiGePS; halide electrolytes, such as Li3InCl6, Li3YCl6, or Li3YBr6; and polymer electrolytes, such as PEO electrolytes, PVDF-HFP electrolytes, or PFEC electrolytes.
[0061] In a preferred embodiment, the electrolyte includes at least one of the following: LATP, LLZO, LLZTO, LiPSCl, LiPSBr, LiSiPS, LiGePS, Li3InCl6, Li3YCl6, Li3YBr6, PEO-type electrolytes, PVDF-HFP-type electrolytes, or PFEC-type electrolytes.
[0062] In a preferred embodiment, the adhesive comprises at least one of polytetrafluoroethylene, styrene-butadiene-styrene block copolymer, polyvinylidene fluoride, polyvinylidene fluoride copolymer, cellulose, nitrile rubber, or modified rubber.
[0063] In a preferred embodiment, the mass ratio of the electrolyte to the adhesive is (95-99.9):(0.1-5);
[0064] Specifically, the mass ratio of sulfide electrolyte or polymer electrolyte to binder is generally (98-99.9):(0.1-2); while oxide electrolyte or halide electrolyte, due to the high hardness of its powder particles and the large friction between the powder particles, generally has a higher proportion of binder by mass, or a small amount (generally not exceeding 10% of the total mass of the system) is added to promote the migration of solvent between powder particles, and the solvent does not react with the system, which can avoid the particles being compacted during the film-making process, but correspondingly, the solvent needs to be removed by drying after rolling.
[0065] The embodiment also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0066] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded, vacuum-sealed, isostatically pressed and then re-sealed to obtain the solid battery.
[0067] Example 1
[0068] This embodiment provides a method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0069] S1-0, Take LiPSCl electrolyte powder and PTFE (polytetrafluoroethylene) binder powder in a mass ratio of 99:1;
[0070] S1-1. At room temperature, the LiPSCl electrolyte powder and the PTFE binder powder are first mixed at 20 rpm for 10 min to obtain intermediate powder.
[0071] S1-2. The intermediate powder is mixed for 1 minute at 2000 rpm at 60°C to obtain a mixed powder.
[0072] S2-1, The mixed powder is rolled twice at 60°C to form the solid electrolyte membrane; wherein,
[0073] In the first rolling process, the speed ratio of the first roller to the second roller is 3, and the gap between the first roller and the second roller is 200 μm; in the final rolling process, the speed ratio of the first roller to the second roller is 1.8, and the gap between the first roller and the second roller is 50 μm.
[0074] The resulting solid electrolyte membrane had a thickness of 50 μm and a density of 1.02 g / cm³. 3The porosity is 46.3%.
[0075] In a preferred embodiment, the diameter of the first roller and the second roller is 15 cm.
[0076] This embodiment also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0077] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0078] Example 2
[0079] This embodiment provides a method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0080] S1-0, Take LiPSCl electrolyte powder and PTFE binder powder in a mass ratio of 99:1;
[0081] S1-1. At room temperature, the LiPSCl electrolyte powder and the PTFE binder powder are first mixed at 20 rpm for 10 min to obtain intermediate powder.
[0082] S1-2. The intermediate powder is mixed for 1 minute at 2000 rpm at 60°C to obtain a mixed powder.
[0083] S2-1, The mixed powder is rolled twice at 60°C to form the solid electrolyte membrane; wherein,
[0084] In the first rolling process, the speed ratio between the first and second rollers is 2, and the gap between the first and second rollers is 200 μm; in the final rolling process, the speed ratio between the first and second rollers is 1.2, and the gap between the first and second rollers is 50 μm.
[0085] The resulting solid electrolyte membrane had a thickness of 50 μm and a density of 1.1 g / cm³. 3 The porosity is 41%.
[0086] In a preferred embodiment, the diameter of the first roller and the second roller is 15 cm.
[0087] This embodiment also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0088] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0089] Example 3
[0090] This embodiment provides a method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0091] S1-0, Take LiPSCl electrolyte powder and PTFE binder powder in a mass ratio of 99:1;
[0092] S1-1. At room temperature, the LiPSCl electrolyte powder and the PTFE binder powder are first mixed at 20 rpm for 10 min to obtain intermediate powder.
[0093] S1-2. The intermediate powder is mixed for 1 minute at 2000 rpm at 60°C to obtain a mixed powder.
[0094] S2-1, The mixed powder is rolled three times at 60°C to form the solid electrolyte membrane; wherein,
[0095] In the first rolling process, the speed ratio of the first roller to the second roller is 3, and the gap between the first roller and the second roller is 200 μm; in the second rolling process, the speed ratio of the first roller to the second roller is 1.8, and the gap between the first roller and the second roller is 50 μm; in the final rolling process, the speed ratio of the first roller to the second roller is 1.2, and the gap between the first roller and the second roller is 30 μm.
[0096] The resulting solid electrolyte membrane had a thickness of 35 μm and a density of 1.25 g / cm³. 3 The porosity is 34.2%.
[0097] In a preferred embodiment, the diameter of the first roller and the second roller is 15 cm.
[0098] This embodiment also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0099] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0100] Example 4
[0101] This embodiment provides a method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0102] S1-0, Take Li3InCl6 electrolyte powder and PTFE binder powder in a mass ratio of 98:2;
[0103] S1-1. At room temperature, the Li3InCl6 electrolyte powder and the PTFE binder powder are first mixed at 50 rpm for 10 min to obtain intermediate powder.
[0104] S1-2. The intermediate powder is mixed for 1 minute at 50°C and 8000 rpm to obtain a mixed powder.
[0105] S2-1, The mixed powder is rolled twice at 50°C to form the solid electrolyte membrane; wherein,
[0106] In the first rolling process, the speed ratio of the first roller to the second roller is 5, and the gap between the first roller and the second roller is 300 μm; in the final rolling process, the speed ratio of the first roller to the second roller is 2, and the gap between the first roller and the second roller is 80 μm.
[0107] The resulting solid electrolyte membrane had a thickness of 80 μm and a density of 1.6 g / cm³. 3 The porosity is 45%.
[0108] In a preferred embodiment, the diameter of the first roller and the second roller is 15 cm.
[0109] This embodiment also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0110] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0111] Example 5
[0112] This embodiment provides a method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0113] S1-0, Take LATP electrolyte powder and PTFE binder powder in a mass ratio of 95:5;
[0114] S1-1. At room temperature, the LATP electrolyte powder and the PTFE binder powder are first mixed at 80 rpm for 10 min to obtain intermediate powder.
[0115] S1-2. The intermediate powder is mixed for 1 minute at 10000 rpm at 50°C to obtain a mixed powder.
[0116] S2-1, The mixed powder is rolled three times at 80°C to form the solid electrolyte membrane; wherein,
[0117] In the first rolling process, the speed ratio of the first roller to the second roller is 5, and the gap between the first roller and the second roller is 200 μm; in the second rolling process, the speed ratio of the first roller to the second roller is 2, and the gap between the first roller and the second roller is 100 μm; in the final rolling process, the speed ratio of the first roller to the second roller is 1.5, and the gap between the first roller and the second roller is 60 μm.
[0118] The resulting solid electrolyte membrane had a thickness of 65 μm and a density of 2.2 g / cm³. 3 The porosity is 39%.
[0119] In a preferred embodiment, the diameter of the first roller and the second roller is 15 cm.
[0120] This embodiment also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0121] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0122] Comparative Example 1
[0123] This comparative example provides another method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0124] S1-0, Take LiPSCl electrolyte powder and PTFE binder powder in a mass ratio of 99:1;
[0125] S1-1. At room temperature, the LiPSCl electrolyte powder and the PTFE binder powder are first mixed at 20 rpm for 10 min to obtain intermediate powder.
[0126] S1-2. The intermediate powder is mixed for 1 minute at 2000 rpm at 60°C to obtain a mixed powder.
[0127] S2-0, A roller press is provided; the roller press includes: two pressing rollers;
[0128] S2-1. The mixed powder is rolled twice at 60°C to form the solid electrolyte membrane; during the two rolling processes, the first roller and the second roller rotate at the same speed, and the gap between the first roller and the second roller is 50 μm.
[0129] The resulting solid electrolyte membrane had a thickness of 50 μm and a density of 1.53 g / cm³. 3 The porosity is 19.5%.
[0130] This comparative example also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0131] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0132] Comparative Example 2
[0133] This comparative example provides another method for preparing a solid electrolyte membrane, the preparation steps of which include:
[0134] S1-0, Take LiPSCl electrolyte powder and SBS (styrene-butadiene-styrene block copolymer) binder powder in a mass ratio of 97:3;
[0135] S1-1. Dissolve the SBS adhesive powder in anisole to obtain an intermediate slurry;
[0136] S1-2. Transfer the LiPSCl electrolyte powder to the intermediate slurry, stir evenly, and obtain a mixed slurry;
[0137] S2-0, A roller coater is provided, the roller coater comprising: two coating rollers;
[0138] S2-1. The mixed slurry is uniformly coated onto a PET base film to obtain an intermediate electrolyte membrane; wherein the gap between the two coating rollers is 50 μm.
[0139] S2-2. The intermediate electrolyte membrane is dried at 70°C for 16 hours to prepare the solid electrolyte membrane.
[0140] The resulting solid electrolyte membrane had a thickness of 50 μm and a density of 1.32 g / cm³. 3 The porosity is 30.5%.
[0141] This comparative example also provides a solid-state battery and its preparation method, the preparation steps of which include:
[0142] S3. After the solid electrolyte membrane as described above is transferred to the solid battery assembly process, the positive electrode, the solid electrolyte membrane and the negative electrode are sequentially die-cut, stacked, welded with tabs, vacuum-sealed, isostatically pressed at 300 MPa for 10 minutes and then re-sealed to obtain the solid battery.
[0143] Detection Examples
[0144] The first-week charge capacity, first-week discharge capacity, first-week efficiency, and full-charge EIS of Examples 1-3 and Comparative Examples 1-2 were tested, and the results are shown in the table below. Figure 1 As shown;
[0145]
[0146]
[0147] As can be seen from the table above, Examples 1-3 are superior to Comparative Examples 1-2 in terms of electrical performance. Among them, Examples 1-3 and Comparative Example 1 both belong to the dry membrane preparation process, but the solid electrolyte membranes prepared by Examples 1-3 have low density and can perform their capacity normally, while the solid electrolyte membranes prepared by Comparative Example 1 have too high density, which affects the capacity performance. Comparative Example 2 belongs to the wet membrane preparation process, and its initial density is slightly higher than that of Example 3, and its capacity performance is also slightly lower than that of Example 3.
[0148] Depend on Figure 1 As can be seen, the initial point of the curve in Comparative Example 1 is basically the same as that in Examples 1-3, but the semicircular arc of Comparative Example 1 is much larger than that in Examples 1-3. This is because the value of the initial point of the curve is mainly composed of the internal impedance of the solid electrolyte membrane, while the value of the semicircular arc is mainly composed of the interfacial impedance of the solid electrolyte membrane. This indicates that Examples 1-3 and Comparative Example 1 have similar internal impedances of solid electrolyte membranes due to the use of the same material, but their interfacial impedances are quite different. This further indicates that the solid electrolyte membranes of Examples 1-3 can significantly improve their interfacial contact with the positive and negative electrodes. In summary, the solid electrolyte membrane prepared by the method of the present invention has low density, high flexibility, good shapeability, and tighter interfacial contact with the active material layer; solid-state batteries including the aforementioned solid electrolyte membrane have significantly improved first-cycle efficiency and first-cycle discharge capacity.
[0149] The above description is merely a preferred embodiment of the present invention and does not limit the implementation and protection scope of the present invention. Those skilled in the art should realize that any equivalent substitutions and obvious changes made based on the description and illustrations of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that the steps include... include: The solid electrolyte membrane is prepared by repeatedly rolling a mixture of electrolyte and binder powder; wherein, In the initial rolling process, the speed ratio between the first and second rollers is 1.2-10; and In the final rolling process, the gap between the first roller and the second roller is 15μm-50μm; and In each rolling process, the speed ratio of the first roller to the second roller is lower than that in the previous rolling process, and the speed ratio of the first roller to the second roller is greater than 1. At the same time, the gap between the first roller and the second roller is lower than that in the previous rolling process. The electrolyte includes at least one of the following: LATP, LLZO, LLZTO, LiPSCl, LiPSBr, LiSiPS, LiGePS, Li3InCl6, Li3YCl6, Li3YBr6, PEO-type electrolytes, PVDF-HFP-type electrolytes, or PFEC-type electrolytes; the adhesive includes at least one of the following: polytetrafluoroethylene, styrene-butadiene-styrene block copolymer, polyvinylidene fluoride, polyvinylidene fluoride copolymer, cellulose, nitrile rubber, or modified rubber.
2. The preparation method according to claim 1, characterized in that, The preparation steps of the mixed powder of the electrolyte and the binder include: S1-0, Take the electrolyte in powder form and the adhesive in powder form; S1-1. The electrolyte and the binder are mixed at a first temperature and a first speed to obtain an intermediate powder. S1-2, At a second temperature and a second speed, the intermediate powder is mixed a second time to obtain the mixed powder; wherein, The first temperature is lower than the second temperature, and the first speed is lower than the second speed.
3. The preparation method according to claim 2, characterized in that, The first mixing process ensures that the electrolyte and the binder are sufficiently and uniformly dispersed to obtain an intermediate powder; the second mixing process filamentizes the binder in the intermediate powder to coat the particles in the intermediate powder into a marshmallow-like shape.
4. The preparation method according to claim 1, characterized in that, The mixed powder further includes a solvent for promoting migration between powder particles, wherein the solvent does not react with the electrolyte or the binder.
5. The preparation method according to claim 1, characterized in that, The mixture of electrolyte and binder powder is rolled several times at 20℃-100℃.
6. The preparation method according to claim 1, characterized in that, The diameter of the first roller and the second roller is 12cm-20cm; the radial runout of the first roller and the second roller is not higher than ±2μm.
7. The preparation method according to claim 4, characterized in that, After the mixed powder is subjected to several rolling processes, the solvent is removed by drying.
Citation Information
Patent Citations
Solid electrolyte, composite integrated positive electrode, integrated battery and preparation method thereof
CN112201848A
Method for producing a solid electrolyte membrane or an anode, and solid electrolyte membrane or anode
US20220029242A1